APPLICATION OF MECHANICAL FILTERS FOR PURIFICATION OF ELECTROLYTE FROM SOLID PRODUCTS OF THE AIR AND ALUMINUM CHEMICAL CELL REACTION - Okorokova, Nadezhda S.; Perchenok, Aleksandr V.; Sevruk, Stanislav D.; Suvorova, Elena V.; Farmakovskaya, Ariadna A.; Kyaw , Aung Thu (Journal of Applied Engineering Science, 2020)
This work presents the results of the development and application of a filtration unit – a cartridge filter with a throttle (discharge) hole – for separating the solid phase – crystalline aluminum hydroxide Al(OH)3, formed during long-term operation of an air and aluminum chemical cell with alkaline electrolyte and power plants based on them. The main theoretical provisions on the filtration mechanism using the discharge hole are formulated, according to which the filtration process consists of two types of filtration – blowout piping and particle coupling. The developed method made it possible to: purify electrolyte with low friction to electrolyte flow at high concentrations of the solid phase (more than 10-15 mass %); ensure long-term performance of the purification system with large masses of the solid phase formed; be able to quickly regenerate the electrolyte; have a small mass and volume; leave a sufficient amount of solid phase in the electrolyte so that the crystals of aluminum hydroxide passing through the filter are a seed for the crystallization of dissolved aluminum in the circuit. The studies carried out allowed us to conclude that the use of mechanical cartridge filters with an orifice hole is an effective and reliable method for cleaning the electrolyte of a power plant with an air and aluminum chemical cell.